Development of a Multiplication Learning Media for Primary School Mathematics using Multiple Math Card - Astriani, Linda; Khairani, Nurul Annisa (FKIP Universitas Lampung, 2022)
This study aims to develop MATHCA (Multiple Math Card) learning media in multiplication material of elementary school grade III. The background of this research is that there are no learning media in the form of cards that have been developed specifically by combining a learning system with a game in the form of cards. The method used in the Research and Development (R&D) uses the method Analysis, Design, Development, Implementation, Evaluation (ADDIE) model. The subjects in the study were third-grade students of SD Negeri 1 Cisantana, Cigugur district, Kuningan Regency. The result showed that media MATHCA was very valid base on the calculation result of media experts, with an average score of 98%, material experts with an average score of 92%, and linguists with an average score of 92%. The result of the practicality test of teachers obtained an average score of 90%, and the results of trials conducted in small groups obtained 96,6%, and in large group, trials obtained a score of 91,1%, this indicates a high level of practicality category in both groups. Thus, it can be concluded that MATHCA learning media that was developed using the ADDIE model is valid and practical to be applied to mathematics learning. Keywords: development model, learning media, ADDIE, multiple math card. DOI: http://dx.doi.org/10.23960/jpmipa/v23i2.pp712-722